Kritische Metaphysik oder Analytische Hermeneutik?: über die Lesbarkeit der Dinge und die apriorischen Voraussetzungen der Bezugnahme - Koch, Anton Friedrich (Deutsche Zeitschrift für Philosophie, 2019)
Kant in his critical metaphysics, as one might call his transcendental philosophy, proceeds from the syncategorematic, subject-sided forms of thinking, which are revealed by general logic qua doctrine of the inferences of reason (i. e. syllogistics), and assigns to them one-to-one categorematic, object-sided forms of thinking: the categories qua pure, non-empirical predicates of things. Kant then shows in his transcendental deduction that the categories are objectively, - i. e. without our invasive intervention - valid of all things in space-time. In the present essay, philosophy is understood not so much as critical metaphysics in a narrow sense of “metaphysics”, but rather as the a priori hermeneutic science; and the transcendental deduction of the categories is replaced by arguments for (1) a readability thesis and (2) a theory of the a priori presuppositions of referencing things in space and time. The readability thesis states that things can be read (1) as world-sided primal tokens (ur-tokens) of proper names of themselves and also (2) as world-sided primal tokens (ur-tokens) of elementary propositions about them. The theory of the a priori presuppositions clarifies the conditions of the possibility of subjects orienting themselves in space and time and being able to refer, first, to themselves qua embodied thinkers and then as well to arbitrary individual items.